Numerical and Analytical Investigation of Stability of the Reinforced Plate - Gaik A. Manuylov; Sergey B. Kositsyn; Irina E. Grudtsyna (Communications - Scientific letters of the University of Zilina, 2021)
The work is aimed at the construction of an algorithm for studying the equilibrium states of a reinforced plate near critical points, using the first (cubic terms) nonlinear terms of the potential energy expansion. Using geometrically nonlinear analysis of displacement, deformation and stress fields, the Eigenforms of buckling were calculated and bifurcation solutions and solutions for equilibrium curves with limit points were constructed depending on the initial imperfections.